Description of Work Attitudes and Positions (Ergonomics) Using the Ovako Work Analysis System (Owas) Method (HEALTH CARE: JURNAL KESEHATAN, 2023)
Introduction: Ergonomics studies the relationship between humans and systems, this is one of the factors that cause musculoskeletal disorders. Nurses are one of the professions that have a high risk of developing musculoskeletal disorders caused by occupational diseases. Due to the an attitude of constant forced labor brought on by an imbalance between workers' responsibilities and talents, occupational disorders develop. This study aims to determine the description of attitudes and work positions (ergonomics) using the ovako work analysis system (OWAS) method for nursing professional students who practice at Arifin Achmad Hospital. Methods: This study uses a descriptive research design. Data were taken by observing using the OWAS method. Results: The results showed that the majority of respondents were 23 years old (60.8%) with most of them being female (84.3%) and the majority having the longest working mass of 7 months (66.7%). The majority of the results obtained after the assessment of attitudes and work positions using OWAS on nursing students when transferring patients needed to be improved (66.7%). Conclusion: most of the respondents after assessing their attitudes and work positions using OWAS on nursing students when transferring patients, it is necessary to improve. Suggestions from this study are to further develop and apply the OWAS method of correct attitudes and work positions (ergonomics) for nurses. Hold a special seminar for nurses on Occupational Health and Safety (K3).Keywords: ergonomics, nursing profession, OWAS, patient mobilization